Obesity and the US military family. (5th September 2013) - Tanofsky‐Kraff, Marian; Sbrocco, Tracy; Theim, Kelly R.; Cohen, L. Adelyn; Mackey, Eleanor R.; Stice, Eric; Henderson, Jennifer L.; McCreight, Sarah J.; Bryant, Edny J.; Stephens, Mark B.
Abstract : Objective: This review discusses the current knowledge and future directions regarding obesity within the US military family (i.e., active‐duty servicemembers, as well as military spouses, children, retirees, and veterans). The increasing rates of overweight and obesity within the US military adversely impact military readiness, limit recruitment, and place a significant financial burden on the Department of Defense. Design and Methods: The following topics are reviewed: 1) The prevalence of and the financial, physical, and psychological costs associated with overweight in military communities; 2) military weight regulations, and challenges faced by the military family related to overweight and disordered eating; 3) the continued need for rigorous program evaluations and new intervention development. Results: Overweight and its associated sequelae impact the entire military family. Military families share many similarities with their civilian counterparts, but they face unique challenges (e.g., stress related to deployments and relocations). Although the military has weight management resources, there is an urgent need for rigorous program evaluation and the development of enhanced obesity prevention programs across the lifespan of the military family—several of which are proposed herein. Conclusions: Interdisciplinary and collaborative research efforts and team‐based interventions will continue to inform understanding of obesity treatment and prevention within military and civilian populations.